TRANSLATION AND CULTURAL ADAPTATION OF THE MEDITERRANEAN DIET QUALITY INDEX IN CHILDREN AND ADOLESCENTS - Miriam Isabel Souza dos Santos Simon; Gabriele Carra Forte; Paulo Jose Cauduro Marostica (Sociedade de Pediatria de São Paulo, 2020)
ABSTRACT Objective: To translate and culturally adapt the Mediterranean Diet Quality Index in Children and Adolescent (KIDMED) for the Brazilian population. Methods: The processes of translation and cultural adaptation followed internationally standardized methodological norms. We used the intraclass correlation coefficient and the Bland-Altman dispersion analysis to assess the reproducibility and calculated the internal consistency with Cronbach's alpha coefficient. Results: A total of 102 children and adolescents participated in the cross-cultural adaptation, of whom 58 (56.9%) were females, with a mean age of 9.8±4.9 years. The mean overall scores of adherence to the Mediterranean diet in the test and retest were similar (8.00 and 3.80 versus 8.01 and 3.84) for children and adolescents, respectively. The intraclass correlation coefficient for children and adolescents was 0.893 and 0.998, respectively. The internal consistency was 0.72. The Bland-Altman plot analysis showed good agreement between the final scores of the test and retest questionnaires, with no statistically significant difference. Conclusions: The KIDMED questionnaire was translated into Brazilian Portuguese and culturally adapted, presenting high reproducibility. This questionnaire can, therefore, be included and used in Brazilian studies that aim at evaluating the adherence to the Mediterranean diet among children and adolescents.